Medical Management of the Diabetic Patient with Coronary Artery Disease - Karastergiou, Kalypso; Kaski, Juan C. (Current Pharmaceutical Design, 2008)
The prevalence of type 2 diabetes is rising at an alarming rate worldwide. Coronary artery disease (CAD) is the leading cause of morbidity and mortality in the diabetic population. Future CAD risk should be routinely assessed in patients with diabetes as specific subgroups might benefit from information derived from cardiac stress testing and other diagnostic procedures. Risk factor control is of paramount importance in all cases and it usually requires sustained lifestyle modifications, coupled with pharmacological interventions. Statins and angiotensin-converting enzyme (ACE) inhibitors are the first-line agents for the treatment of dyslipidaemia and hypertension, respectively. Microvascular, but not macrovascular, complications of diabetes are effectively prevented by good glycaemic control. Metformin is considered the first-choice agent in overweight diabetic subjects, while the role of thiazolidinediones is currently the focus of medical research. The diagnosis of acute coronary events in patients with diabetes is often challenging because of the high prevalence of silent ischaemia in these subjects. All acute cardiac events need to be promptly treated and myocardial reperfusion attempted without delay. Maintaining glucose levels as close to normal as possible, during and shortly after an acute event, improves prognosis in patients with diabetes. Risk factor control remains the cornerstone of secondary prevention; beta-blockers, ACE-inhibitors and antiplatelet agents confer additional symptomatic and survival benefit. Similar therapeutic principles also apply to patients with type 1 diabetes. This article addresses the complex problem of managing patients with diabetes and coronary artery disease.
Keywords: coronary artery disease